Pengaruh Pendidikan Agama pada Anak dalam Keluarga Beda Agama di Desa Klepu Sooko Ponorogo - Prahara, Erwin Yudi (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2016)
This research aims to discuss a phenomenon of interfaith family in Klepu village, Sooko district, Ponorogo regency in the context of religious education transformation in family. This study was qualitative research. The subjects of the research are Islamic and catholic family, mixed faith family as well. The data were collected through observation, interview, and documentation. The result of the research indicates that mother religiosity is more dominant in influencing childrenâs religious upbringing. Nine informants showed that four cases of children religiosity follows religion of their mother, three cases of children religiosity follow religion of their father and father is religiously active, two cases of children religiosity is questionable because they are still baby. This situation happens because the family couple does not have agreement to be bound or there is an agreement containing a freedom for their children. This is because the communication between mother and children is more intense compared to father and children communication. Dominant figure of mother cannot be separated from her nurture and her more time to interact with her childrenØØ§ÙÙØª ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹Ø±Ø¶ Ø¸Ø§ÙØ±Ø© Ø§ÙØ£Ø³Ø±Ø© Ø§ÙØ«ÙØ§Ø¦ÙØ© Ø¯ÙÙÙØ§ ÙÙ ÙØ±ÙØ© ÙÙÙÙÙ Ø³ÙÙÙ ÙÙÙÙØ±ÙØºÙ ÙÙ Ø³ÙØ§Ù ØªØÙÙÙ Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© ÙÙ Ø§ÙØ£Ø³Ø±Ø©. Ø§ØªÙØ¨Ø¹Øª ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙÙÙÙØ¬ Ø§ÙÙÙÙÙØ ÙÙØµØ§Ø¯Ø± Ø¨ÙØ§ÙØ§ØªÙØ§ Ø§ÙØ£Ø³Ø±Ø© Ø§ÙÙØ³ÙÙØ© ÙØ§ÙØ£Ø³Ø±Ø© Ø§ÙÙØ§ØªÙÙÙÙÙØ© ÙØ§ÙØ£Ø³Ø±Ø© Ø§ÙØ«ÙØ§Ø¦ÙØ© Ø¯ÙÙÙØ§. Ø£ÙØ§ Ø£Ø³Ø§ÙÙØ¨ Ø¬ÙØ¹ Ø§ÙØ¨ÙØ§ÙØ§Øª ÙÙØ°Ø§ Ø§ÙØ¨ØØ« ÙØ§ÙÙÙØ§ØØ¸Ø© ÙØ§ÙÙÙØ§Ø¨ÙØ© Ø§ÙØ´Ø®ØµÙØ© ÙØ§ÙÙØ«Ø§Ø¦Ù Ø§ÙÙÙØªÙØ¨Ø©. Ø¯ÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¹ÙÙ Ø£Ù Ø§ÙØ£Ù ÙÙØ§ ØªØ¯ÙÙ Ø¨Ù ØªØ¤Ø«ÙØ± ÙØ«ÙØ±Ø§ ÙÙÙØ§ ÙØ¯ÙÙ Ø¨Ù Ø§ÙØ§Ø¨Ù. ÙÙÙ Ø³ØªØ© Ø§ÙÙØ®Ø¨Ø±ÙÙ Ø§ÙÙØ¨ØÙØ«ÙÙ Ø¯ÙÙØª Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¹ÙÙ Ø£Ù Ø£Ø±Ø¨Ø¹Ø© ÙÙÙÙ Ø§ØªØ¨Ø¹ÙØ§ Ø¯ÙÙ Ø£ÙÙÙØ ÙØ«ÙØ§Ø«Ø© ÙÙÙÙ Ø§ØªÙØ¨Ø¹ÙØ§ Ø¯ÙÙ Ø£Ø¨ÙÙÙ ( Ø¥Ø°Ø§ ÙØ§Ù Ø§ÙØ£Ø¨ ÙØ¹ÙØ§ÙØ§ ÙÙ Ø§ÙØ£Ø³Ø±Ø© )Ø ÙØ§Ø«ÙØ§Ù ÙÙÙÙ ÙÙ ÙÙÙÙØ§ ÙØ§Ø¶ØÙÙ ÙÙÙÙÙÙØ§ ÙÙ Ø³Ù ÙØ¨Ù Ø§ÙØ®Ø§ÙØ³Ø©. ÙÙØ¹Øª ÙØ°Ù Ø§ÙØØ§ÙØ© Ø®Ø§ØµØ© ÙÙ Ø§ÙØ£Ø³Ø±Ø© Ø§ÙØªÙ ÙÙØ³ ÙÙÙØ§ Ø§ØªÙÙØ§Ù ÙÙØ²Ù Ø£Ù Ø¨ÙÙ Ø§ÙØ²ÙØ¬ÙÙ Ø§ØªÙÙØ§Ù ÙÙÙÙÙÙÙØ§ ÙØ¹Ø·ÙØ§Ù Ø§ÙØØ±ÙÙØ© ÙÙØ£Ø¨ÙØ§Ø¡ ÙÙ Ø§Ø®ØªÙØ§Ø± Ø§ÙØ¯ÙÙ. ÙÙØ¹Øª ÙØ°Ù Ø§ÙØ¸Ø§ÙØ±Ø© ÙØ£Ù ÙÙÙØ© Ø§ÙØ§ØªØµØ§Ù Ø¨ÙÙ Ø§ÙØ£Ø¨ÙØ§Ø¡ ÙØ¨ÙÙ Ø§ÙØ£Ù Ø£ÙØ«Ø± ÙÙ ÙÙÙØ© Ø§ÙØ§ØªØµØ§Ù Ø¨ÙÙÙÙ ÙØ¨ÙÙ Ø¢Ø¨Ø§Ø¦ÙÙ. Â ÙØ§ÙØª ÙÙÙÙØ© Ø§ÙØ£Ù ÙÙ Ø§ÙØ£Ø³Ø±Ø© ÙØ§ ØªÙÙØµÙ Ø¹Ù ÙÙÙÙØ§ Ø£ÙØ§ ÙÙØ£Ø¨ÙØ§Ø¡ ÙØ·ÙÙ Ø§ØªØµØ§ÙÙØ§ Ø¨Ø§ÙØ£Ø¨ÙØ§Ø¡.